Employee protection shocks and corporate cash holdings - Beuselinck, Christof; Markarian, Garen; Verriest, Arnt (Journal of Corporate Finance, 2021)
We examine the relation between employee protection legislation and corporate cash holdings. Our rationale rests on the notion that higher labor adjustment costs increase a firm's operating leverage making firms to adjust their liquidity management by increasing precautionary savings. Consistent with this, we show that the staggered passage of legal exceptions to the “at-will” employment doctrine in various U.S. states led to an average increase in cash holdings by 7.2%. Cash increases are higher when unionization rates and industry concentration are lower, and when industry discharge rates and volatility is higher. Consistent with the financial flexibility argument of tighter employment protection increasing corporate cash needs, the value of cash increases after the passage of pro-labor regulations. Moreover, we find that the increase in the value of cash is especially pronounced for financially constrained firms.